Piano a quatro mãos: aspectos interpretativos e obras brasileiras para essa formação - Sandra Costa Almeida de Lino Faria (2007)
This research presents a catalogue with 62 four-hand piano works of Brazilian composers, listed in the Musicon CDMC of the Universidade de Campinas. Seven works were examined, from an analytical and interpretative viewpoint. The article contains also a four-hand pianos historic introduction and excerts of interviews with five Brazilian pianos duets.